Metode Penyelesaian Masalah Cauchy Degenerate Melalui Masalah Cauchy Nondegenerate = A method for solving of degenerate Cauchy problems via nondegenerate Cauchy problems - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT In this thesis we investigate how to solve the abstract degenerate Cauchy problems via abstract nondegenerate Cauchy problems. The problems are discussed in the Hilbert space H which can be written as an orthogonal direct sum of Ker M and (Ran M*) . By certain assumptions, abstract degenerate Cauchy problems can be reduced to abstract nondegenerate Cauchy problems. If we have the solution of abstract nondegenerate Cauchy problems, then by certain transformation we can find the solution of abstract degenerate Cauchy problems.